2021
DOI: 10.1155/2021/5582648
|View full text |Cite
|
Sign up to set email alerts
|

Cediranib Induces Apoptosis, G1 Phase Cell Cycle Arrest, and Autophagy in Non-Small-Cell Lung Cancer Cell A549 In Vitro

Abstract: Lung cancer remains the leading cause of cancer death worldwide. Late diagnosis, chemoresistance, and metastasis are the main reasons for the high mortality rate of lung cancer. Therefore, the development of other treatments is urgent. Cediranib (CED), a vascular endothelial growth factor receptor (VEGFR) kinase inhibitor, shows promising antitumour activities in various cancers including lung cancer. Here, we explored the effects and the underlying molecular mechanism of CED on non-small-cell lung cancer (NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Having found that G0/G1 cell cycle arrest was responsible for the increasing in SARS-CoV-2 RNA replication, we next focused on the cellular pathways involved in the G0/G1 stage ( Figure 5 A) in order to understand which pathways are important for SARS-CoV-2 replication. To do this, we used several compounds that are known to block the cell cycle in G0/G1 in A549 cells (Palbociclib [ 25 ], Abemaciclib [ 26 , 27 ], Gefitinib [ 28 ], Cediranib [ 29 ], Resveratrol [ 30 ], and Hesperidin [ 31 ]). These compounds target different pathways described in Figure 5 B. Inhibitors of growth factor receptors (EGFR and VEGFR) tyrosine kinase (Gefitinib and Cediranib) led to an increase in SARS-CoV-2 infection ( Figure 5 C).…”
Section: Resultsmentioning
confidence: 99%
“…Having found that G0/G1 cell cycle arrest was responsible for the increasing in SARS-CoV-2 RNA replication, we next focused on the cellular pathways involved in the G0/G1 stage ( Figure 5 A) in order to understand which pathways are important for SARS-CoV-2 replication. To do this, we used several compounds that are known to block the cell cycle in G0/G1 in A549 cells (Palbociclib [ 25 ], Abemaciclib [ 26 , 27 ], Gefitinib [ 28 ], Cediranib [ 29 ], Resveratrol [ 30 ], and Hesperidin [ 31 ]). These compounds target different pathways described in Figure 5 B. Inhibitors of growth factor receptors (EGFR and VEGFR) tyrosine kinase (Gefitinib and Cediranib) led to an increase in SARS-CoV-2 infection ( Figure 5 C).…”
Section: Resultsmentioning
confidence: 99%
“…Originally, apatinib was regarded as an anti-angiogenesis inhibitor against VEGFR-2, similar to drugs of a similar type, namely, sorafenib, sunitinib, and cabozantinib ( 31 ). Considering the limited efficiency of other anti-angiogenesis inhibitors, such as cediranib ( 32 ) in advanced NSCLC, it is rather possible that mechanism of apatinib may be different ( 33 ). Apatinib may also possess other targets, such as RET, FlT3, and so on ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Combined therapy with rapamycin and suberoylanilide hydroxamic acid may also increase radiosensitivity in these cells and inhibiting the levels of autophagy can markedly weaken the radiotherapy sensitivity caused by this combined treatment, thus suggesting that the inhibitory effect of combination therapy may be partially due to the induction of autophagy in NSCLC ( 79 ). Cediranib has also been shown to exhibit effective anti-tumor activities in NSCLC cells by inducing G 1 phase cell cycle arrest and autophagy via the MAPK/Erk1/2 and Akt/mTOR pathways in A549 cells ( 80 ).…”
Section: The Role Of Pcd In the Metastasis Of Nsclcmentioning
confidence: 99%